Chemical Reactivity and Reaction Paths - Klopman, Gilles. (John Wiley and Sons, 1974)
Chemical Reactivity and Reaction Paths. Empirical and Semiempirical Calculations of chemical Reactivity and Reaction paths. Intermolecular Interactions and Chemical Reactivity. The Generalized Perturbation Theory of chemical Reactivity and Its...